Helicopter Parenting among Late Adolescents (IAHS Medical Journal, 2024)
Background: In the contemporary context, helicopter parenting which is a common practice and in Southeast Asia region, it is a growing parenting approach. It has several components that affect adolescents and emerging adults physical, psychological and social well-being. The aim of the study is to measures the parenting style for the adolescent for which the Helicopter Parenting Scale (HPS) was used.Material and methods: A cross-sectional study was conducted to assess the state of helicopter parenting style of parents on late adolescents of Police Lines School and College, Rangpur, Bangladesh.Results: The mean age of the adolescent was 17.7±0.6 years. The mean of HP scores was 3.6±0.5. About three out of five participants had a perceived average level of HP (58.9%) and a few of them had a high level of HP (2.3%). A statistically significant association found within the level of HP and adolescent’s family type (p